Developing a framework for make-or-buy decisions - Cánez, L.E.; Platts, K.W.; Probert, D.R. (International journal of operations & production management, 2000)
The make-or-buy question represents a fundamental dilemma faced by many companies. Companies have finite resources and cannot always afford to have all manufacturing technologies in-house. This has resulted in an increasing awareness of the importance of make-or-buy decisions. This paper reports on the development of a make-or-buy framework to address the make-or-buy decision for either a specific individual part or family of parts. Firstly, a literature review of the principal make-or-buy approaches is discussed. Secondly, the development of a make-or-buy framework is described and the framework is explained and illustrated using case studies. Thirdly, the operationalisation of the framework is outlined. The paper concludes with a discussion of its contribution to both the academic understanding of the subject, and the improvement of industrial practice.